Teaching Vocabulary Using Flash Cards in Indonesian ESP Classroom: A One-Shot Case Study - Hardiyanti, Rani Linggar Purga; Herda, Rozanah Katrina (Journal of Education, Language Innovation, and Applied Linguistics, 2023)
It can be denied that teaching vocabulary to ESP students is challenging since they need treatment to learn it on the right target. 21st-century learning requires the students, no exception the ESP students, to fulfill the demands of the 4Cs (Collaboration, Communication, Creativity, and Critical Thinking), which makes students show language competence in the right target. This quantitative study with a one-shot case study aims to explore the knowledge level regarding vocabulary learning using Flash Cards and reveal the students' activities during learning using Flash Cards. Thirty-one participants from one vocational high school were involved in this study. The researchers used two types of instruments, namely, test and observation. The results of this study showed that students’ scores in vocabulary testing indicating their knowledge of language word level were categorized ‘good’ by the mean score of 73.97. Additionally, they showed enthusiasm in learning vocabulary using Flash Card. The role of Flash Cards in teaching vocabulary in ESP classrooms benefits students in grasping the meaning of L2 words that can be used or applied in the language context. Keywords: Teaching Vocabulary; ESP; Flash Card.